The Effect of Acoustic Pressure and Cavitation on the Secondary Nucleation of Ice - Yu Deyang; Liu Baolin; Wang Bochun (Zhileng xuebao, 2011)
In order to clarify the mechanism of secondary nucleation of iceinduced by ultrasound, experiments on ice crystals in degassed sucrose solutions and untreated solutions have been carried out using a novel ultrasonic cold stage device. For each experiment, the ultrasonic waves operated at a power output of 120W. The results show that the ice dendrite crystals growing in a sucrose solution can be broken up into smaller fragments when ultrasound was applied for 2 s, but the pre-existing ice dendrite crystals in a degassed sucrose solution are still unbroken when ultrasound was applied for 6 s. These findings confirm that cavitation induced by ultrasound is a major factor for the fragmentation of ice crystals.